Lokal von, global ambisjon. Framveksten av småkraftverk i Noreg etter 2000 - Gunnar Yttri (Heimen)
Abstract Since 2000, extensive expansion of small hydropower has taken place in Norway. Landowners and power companies have played key roles. This study from the County of Sogn and Fjordane and the national level indicates that differences in the publicly owned companies' strategies can explain the widely different ways small power plants got organized and owned. Regional power companies empowered farmers to establish independent and self-owned power plants, while power companies operating on a national level signed long-term lease contracts of waterfalls with landowners and took control of the plants. These contracts and power plants were later sold to foreign companies.